Genetic characterization of highly pathogenic avian influenza A H5N8 viruses isolated from wild birds in Egypt - Kandeil, Ahmed; Kayed, Ahmed; Moatasim, Yassmin; Webby, Richard J.; McKenzie, Pamela P.; Kayali, Ghazi; Ali, Mohamed A. (Journal of general virology, 2017)
A newly emerged H5N8 influenza virus was isolated from green-winged teal in Egypt during December 2016. In this study, we provide a detailed characterization of full genomes of Egyptian H5N8 viruses and some virological features. Genetic analysis demonstrated that the Egyptian H5N8 viruses are highly pathogenic avian influenza viruses. Phylogenetic analysis revealed that the genome of the Egyptian H5N8 viruses was related to recently characterized reassortant H5N8 viruses of clade 2.3.4.4 isolated from different Eurasian countries. Multiple peculiar mutations were characterized in the Egyptian H5N8 viruses, which probably permits transmission and virulence of these viruses in mammals. The Egyptian H5N8 viruses preferentially bound to avian-like receptors rather than human-like receptors. Also, the Egyptian H5N8 viruses were fully sensitive to amantadine and neuraminidase inhibitors. Chicken sera raised against commercial inactivated avian influenza-H5 vaccines showed no or very low reactivity with the currently characterized H5N8 viruses in agreement with the genetic dissimilarity. Surveillance of avian influenza in waterfowl provides early warning of specific threats to poultry and human health and hence should be continued.